Distribution of a distance in an ovaloid - Gečiauskas, E. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. Гячяускас. Распределение расстояния внутри овалоида E. Gečiauskas. Atstumo pasiskirstymas ovaloide